2005
DOI: 10.1136/jnnp.2004.042952
|View full text |Cite
|
Sign up to set email alerts
|

The corpus callosum in first episode schizophrenia: a diffusion tensor imaging study

Abstract: Background: Neuropathological and imaging studies suggest that corpus callosum abnormalities (CC) are present in schizophrenia, but it remains to be determined whether these abnormalities are present at illness onset. Diffusion tensor imaging (DTI), which is more sensitive than conventional magnetic resonance imaging (MRI) in detecting subtle structural changes in the organisation and integrity of white matter tracts, is an ideal tool to investigate this question. Objective: To determine whether CC abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 27 publications
7
67
1
Order By: Relevance
“…The spread of the FA distribution along the tract was skewed in the patients, which is thought to represent reduced FA in the core of the tract. In accordance with another first-episode study [13] , we found no abnormalities in the genu or splenium of the corpus callosum. In contrast, Cheung et al [16] did find reduced FA in the splenium of the corpus callosum in medication-naive firstepisode patients.…”
Section: Discussionsupporting
confidence: 92%
“…The spread of the FA distribution along the tract was skewed in the patients, which is thought to represent reduced FA in the core of the tract. In accordance with another first-episode study [13] , we found no abnormalities in the genu or splenium of the corpus callosum. In contrast, Cheung et al [16] did find reduced FA in the splenium of the corpus callosum in medication-naive firstepisode patients.…”
Section: Discussionsupporting
confidence: 92%
“…Postmortem studies have shown a genderdiagnosis effect of reduced axonal number (Highley et al, 1999a), oligodendrocyte density loss (Hof et al, 2003), and lower levels of immunoreactivity of oligodendrocyte-associated proteins in the genu of the corpus callosum (Flynn et al, 2003). Diffusion-weighted imaging has been relatively consistent in reporting reduced callosal FA in chronic schizophrenia (Douaud et al, 2007;Koch et al, 2010;Kubicki et al, 2008;Miyata et al, 2010;Mori et al, 2007b;RotarskaJagiela et al, 2008), including during remission (Koch et al, 2010) and less consistently in studies examining individuals at the first episode (Cheung et al, 2008;Gasparotti et al, 2009;Perez-Iglesias et al, 2010b;Peters et al, 2008;Price et al, 2005;Szeszko et al, 2005) or in earlier stages of illness (Davenport et al, 2010;Douaud et al, 2007;Kyriakopoulos and Frangou, 2009). Directly comparing first episode and chronic groups supports more severe changes in FA in the genu of the corpus callosum (Friedman et al, 2008;Kong et al, 2011), the left ILF (Friedman et al, 2008), and ALIC (Bora et al, 2011) in the chronic group including relative to the first episode group.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies highlight the progressive nature of these deficits. In WM, a single study of individuals experiencing their first psychotic episode did not detect microstructural changes (as assessed by DTI) in the corpus callosum relative to healthy controls (Price et al, 2005). Studies including both first episode and chronic patients showed that patients with chronic disease had significantly reduced FA compared with controls, reaching only a trend level in first episode patients (Friedman et al, 2008;Kong et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…For example, Pomarol-Clotet and colleagues 28 reported a positive finding in patients with chronic schizophrenia, but Peters and colleagues 9 and Price and colleagues 29 could not detect corpus callosum abnormalities in patients with first-episode schizophrenia, nor in participants at ultra-high risk for psychosis. Most interestingly, Friedman and colleagues 30 conducted a cross-sectional DTI study including patients with firstepisode and chronic schizophrenia and obtained similar findings to those of our current study: less prominent changes in white matter at illness onset that progress in more chronic states of illness.…”
Section: Discussionmentioning
confidence: 99%